High performance 1.3µm InAs quantum dot lasers epitaxially grown on silicon - Liu, Alan Y.; Zhang, Chong; Snyder, Andrew; Lubychev, Dimitri; Fastenau, Joel M.; Liu, Amy W.K.; Gossard, Arthur C.; Bowers, John E. (OFC 2014, 2014)
We demonstrate 1.3 µm InAs quantum dot lasers on silicon by molecular beam epitaxial growth with low thresholds (16 mA), high output power (>50 mW), high T0 (>200 K), and high temperature lasing (115 °C).